Aplicación de fungicidas para controlar sigatoka negra mycospharella fijiensis morelet mediante dos tipos de bomba en platilla de banano - Paladinez Granda, Josenka Yannuzelli (2018)
The present work was carried out in the Granja Santa Inés, in the experimental area of banana of the Academic Unit of Agricultural Sciences, of the Technical University of Machala, located in km. 5,5 vía al Cambio, in the Machala canton, province of El Oro. One of the most serious problems facing the country is the presence of black Sigatoka, showing damage to the leaves with severe injuries, known as pinches and stretch marks that As the fungus increases its attack, necrotic spots are observed that reduce the photosynthetic activity causing alterations in its physiology, minimizing the productivity of the crop, diminishing the quality of the fruit and the profitability, thus generating losses of up to 100%. Small farmers is the lack of resources to hire equipment such as aircraft application because of the high costs and the size of the farm which requires the use of terrestrial equipment, the theme of the investigation was Application of fungicides to control black Sigatoka "Mycospherella fijiensis, M. Using two types of pump in banana template, within the general objectives is to determine which type of pump helps to better control this disease, within the specific objectives considered, to determine the best of the treatments between the fungicides Bravo and Banana Film in the control of black Sigatoka in a banana template, in addition to evaluate which is the best application equipment between the electrostatic and motor pump, and to evaluate the smallest area under the curve of progress of the disease. The data evaluated were, progression of disease severity at 7, 14, 21, 28, 35, 42 and 49 days after application on leaf 2 and 3 of the plants selected for each treatment, the experimental design was random block, with 5 treatments and 5 repetitions. The Anova table breaks down the variance by effect of the fungicides applied in sheet 2 AUDPC, using two types of pump where the coefficient of variation reached 13.76%, while the area under the disease progress curve in sheet 2 with two pump types was T1, (187.45) instead in the evaluation by weeks of the progress of black Sigatoka disease in leaf 2, reached the lowest value for T1 in both fumigation pumps whose value was less than 30% while for the other treatments they reached a higher percentage of severity, for the effect of fungicide in sheet 3 using the two types of pumps, the Anova has a coefficient of variation of 9.91%, the area under the disease progress curve in sheet 3 with two types of pumps was determined that the T1 treatment was lower with 230.84% and for the evaluation by weeks of the progress of the disease in sheet 3, it reached values lower than 30%. In all treatments, the Bravo fungicide at a dose of 1.75 plus Banana Film at 1 liter was the one with the lowest degree of infection on leaves 2 and 3 with two types of pumps.